Feasibility of Laboratory Facilities and Infrastructure in the Machining Practice Course in the Mechanical Engineering Education Study Program - Kusumayanti, Nadia; Harlin, Harlin (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to assess the feasibility of laboratory facilities and infrastructure in supporting the implementation of machining practice courses in the Mechanical Engineering Education Study Program. This study uses a qualitative descriptive method with data collection techniques through direct observation, interviews, and documentation with source triangulation, technique triangulation, and time triangulation. The results of the study indicate that in general the lathe laboratory has met the eligibility standards according to Permendiknas No. 40 of 2008. However, there are still shortcomings such as the limited number of machines, lack of measuring instruments, and the need for regular maintenance of equipment. Laboratory facilities are considered adequate, but not yet ideal to support effective and efficient practicum activities. Therefore, an active role is needed from lecturers and faculty in evaluating, maintaining, and developing facilities. In addition, institutions are also advised to review the practicum schedule so that laboratory utilization is more optimal and equitable for all students.